Seedling production of Brazilian native species by inoculation of arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria - Kayashima, Momoko (2021)
The success of reforestation contributes to biodiversity, and the use of seedlings of native species with good quality in these areas is essential. In this study, three native Brazilian plants were focused: macauba (Acrocomia aculeata (Jacq.) Lodd. ex Mart.), canafistula (Peltophorum dubium (Spreng.) Taub.) and pau-viola (Citharexylum myrianthum Cham.). These plants are considered pioneer species, and biological inputs such as microbial inoculants in the soil are significant to the seedling establishment that can be applied to develop high-quality seedling production. Thus, the objective of this work was to evaluate the seedling’s growth inoculated with beneficial microorganisms, arbuscular mycorrhizal fungi (AMF), produced by on-farm method, and Plant Growth Promoter Rhizobacteria (PGPR), isolated from native Brazilian tree species. We assessed the seedlings growth and microbial community in the soil by PCR-DGGE technique. We detected no effect of AMF inoculation in the biomass accumulation of macauba, but higher AMF colonization was confirmed when we inoculated in the early stage. Additionally, it was revealed that 90 % of similarity on the AMF community in the soil between inoculated seedlings and non-inoculated ones by the PCR-DGGE technique, which probably explain why the plant biomass was not accumulated by AMF inoculation. Conversely, AMF inoculation increased canafistula and pau-viola seedling’s growth. Canafistula seedling also responded positively to PGPR inoculation as well as the combination of AMF and PGPR inoculation. Consequently, the AMF and PGPR inoculation contribute to the seedling's production with sustainability and soil quality. Therefore, we assessed that the different responses to inoculation with FMA and PGPR among native forest species. Additional studies are required to investigate the effect of bioinoculant on the seedling’s growth and the tolerate biotic and abiotic conditions in the field. Keywords: Beneficial microorganism. Symbioses. On-farm.